2014
DOI: 10.1088/0031-9155/60/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bias and variance in low-count OSEM list mode reconstruction

Abstract: Statistical algorithms have been widely used in PET image reconstruction. The maximum likelihood expectation maximization (MLEM) reconstruction has been shown to produce bias in applications where images are reconstructed from a relatively small number of counts. In this study, image bias and variability in low-count OSEM reconstruction are investigated on images reconstructed with MOLAR (motion-compensation OSEM list-mode algorithm for resolution-recovery reconstruction) platform. A human brain ([11C]AFM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…As a consequence, scatter is overestimated and scatter corrected activity negatively biased, as hypothesized also by other authors. 30,31 Inclusion of TOF and PSF information makes the reconstruction less sensitive to inaccurate scatter estimates 32 and thereby results in an improved quantification under high RFs and small true numbers. Further reconstruction attempts including a scatter correction without scaling of the simulated scatter estimate to the measured emission data and/or with an increased number of iterations of the underlying single scatter simulation have been investigated, but could not improve quantification by the OSEM algorithm in the late measurement frames.…”
Section: A Phantom Imagingmentioning
confidence: 99%
“…As a consequence, scatter is overestimated and scatter corrected activity negatively biased, as hypothesized also by other authors. 30,31 Inclusion of TOF and PSF information makes the reconstruction less sensitive to inaccurate scatter estimates 32 and thereby results in an improved quantification under high RFs and small true numbers. Further reconstruction attempts including a scatter correction without scaling of the simulated scatter estimate to the measured emission data and/or with an increased number of iterations of the underlying single scatter simulation have been investigated, but could not improve quantification by the OSEM algorithm in the late measurement frames.…”
Section: A Phantom Imagingmentioning
confidence: 99%
“…Many previous works have focused on the behavior of statistical PET reconstructions in low-count conditions (18,(20)(21)(22)(23)(24)(25) and typically characterized image quality in terms of noise and bias. However, more work is needed to translate the implications of these findings for specific clinical tasks.…”
mentioning
confidence: 99%
“…Previous work has demonstrated that MOLAR can produce images with minimal bias, even at very low counts. 38 While the kinetic parameters estimated by the indirect method were not free from bias, the CoV versus bias curves of the parameters estimated by the indirect method were largely overlapping for the two count levels assessed in this work, suggesting that bias in kinetic parameters is not strictly related to the number of counts in a frame. However, fewer subsets were used than is standard practice (12 vs. 21), and the counts per subset may be the more important determining factor in low-count bias.…”
Section: D Low-count Biasmentioning
confidence: 66%